The role of travel mode in engagement with a Radio Frequency ID chip based school physical activity intervention - Emma Coombes (Frontiers Media S.A., 2015)
Background: The prevalence of active travel to school in children is low and declining. For example, the 2014 National Travel Survey showed that just 46% of primary school children walk to school. This is despite the fact that children who actively travel have been shown to be more physically active overall as well as perform better in class. Beat the Street is a community based intervention which uses RFID (Radio Frequency ID) chip readers attached to locations around the neighbourhood. The aim of the intervention is to encourage walking and cycling by gamifying these travel behaviours; individuals taking part gain points by touching a smartcard on the readers and these points become part of a competition. One of the aims of Beat the Street is to encourage children who already walk and cycle to and from school to do so more, as well as achieve modal shift from motorised transport to active travel as a means of commuting. However, habitual travel mode is 'sticky' and, despite the potential health benefits being greater, it may be more difficult to change mode than it is to encourage more activity in those who already walk or cycle. Set in a neighbourhood in the city of Norwich, England, this analysis examines how travel mode prior to the initiation of Beat the Street is associated with subsequent engagement with the intervention and what the association of this engagement is with physical activity change. Aim: This pilot study evaluates how prior travel mode to school is associated with engagement in the Beat the Street intervention in schoolchildren in the city of Norwich, England. Methods: The Beat the Street intervention was conducted within a Norwich neighbourhood for 9 weeks during May-July 2014. Children were recruited to the evaluation via two schools; one in the intervention neighbourhood, and a control located on the opposite side of the city. All year 4 and 5 children (aged 8-10 years) were invited at both schools. Recruited children completed a travel diary that recorded their mode of travel to school (active or non-active) for 1 week at baseline (Week 0), mid-intervention (Week 7), and 3 months post-intervention (Week 20). Engagement with the intervention was measured by identifying the total number of times each child touched a Beat the Street RFID reader with their smartcard across the 9 weeks, with this information being automatically stored by the RFID readers. Based on this data, children were classified as having either 'no', 'low' or 'high' engagement with the intervention. Finally, to measure children's physical activity levels, each participant wore an accelerometer during all three measurement periods, and from accelerometery we derived mean counts per minute (CPM) for each measurement occasion. We then examined differences in levels of engagement with the intervention by travel mode to school, and subsequent changes in physical activity, using linear models. Results: Fifty-one children (34.0%) participated at the intervention school and 29 (51.8%) at the control. We found that engagement with the intervention was highest amongst those actively travelling to school at baseline with individuals making 99.9 smartcard touches across the 9 weeks (95%CI 34.5, 165.3), versus 35.9 (2.4, 69.4) for non-active travellers and 24.0 (11.8, 36.2) for those using a mix of active and non-active travel. However, those individuals who were non-active travellers at baseline but switched to become active travellers at post-intervention had the highest levels of engagement overall (192.5 smartcard touches, 95%CI 84.5, 300.5). Those children who engaged with the intervention the most experienced the greatest increase in physical activity. For example, children with high levels of engagement increased their physical activity by +13.1CPM (95%CI -30.9, 57.0) during the morning commute to school, whereas those with low levels of engagement experienced a smaller increase in physical activity of +1.3CPM (-22.5, 25.0), and those who did not engage with the intervention experienced a decrease in physical activity of -5.1CPM (-18.0, 7.7) across the study. Conclusions: In conclusion, we found that engagement with Beat the Street was highest amongst those children already active travelling to school, with non-active travellers plus those using a mix of active and non-active modes showing much lower levels of engagement with the intervention. Furthermore, children who demonstrated high levels of engagement with the intervention experienced an increase in physical activity, compared to the decline experienced by those who did not engage. These findings suggest that prior travel behaviours were associated with uptake of this intervention and whilst Beat the Street successfully encouraged active children to undertake more activity, a challenge remains for technology based physical activity interventions to find novel ways to engage and support individuals to switch from inactive behaviours to becoming active.